2006
DOI: 10.1071/bt05041
|View full text |Cite
|
Sign up to set email alerts
|

Distributional pattern of plant species endemic to the Northern Territory, Australia

Abstract: The distributions of the 567 plant species considered to be endemic to the Northern Territory, Australia, were collated from a distributional database comprising about 600 000 records. Endemic species comprise a non-random taxonomic subset of all plants known from the Northern Territory. Because of substantial geographic disparity in collecting effort, we analysed geographic patterning of these endemic species by using both (1) actual records only and (2) interpolated ranges (minimum convex polygons). The geog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 44 publications
1
46
0
Order By: Relevance
“…the Mitchell Plateau and Prince Regent River region) (Woinarski 1992;McKenzie et al 2009). Woinarski et al (2006) similarly demonstrated that endemic plant species richness in the Northern Territory was predicted by topographic complexity and rainfall, with higher richness in high-rainfall and topographically complex areas. As discussed above, the high rainfall areas support more monsoon rainforest which is an important resource for many species including numerous endemics (e.g.…”
Section: Endemics On Islandsmentioning
confidence: 75%
“…the Mitchell Plateau and Prince Regent River region) (Woinarski 1992;McKenzie et al 2009). Woinarski et al (2006) similarly demonstrated that endemic plant species richness in the Northern Territory was predicted by topographic complexity and rainfall, with higher richness in high-rainfall and topographically complex areas. As discussed above, the high rainfall areas support more monsoon rainforest which is an important resource for many species including numerous endemics (e.g.…”
Section: Endemics On Islandsmentioning
confidence: 75%
“…Woinarski et al 2006a). It has also provided the necessary environment for the development of the richest rock art galleries in the world.…”
Section: Landformsmentioning
confidence: 99%
“…Some parts of Northern Australia have notably high species richness or endemism. The Kimberley supports about 2000 species of native plants (Wheeler et al 1992), of which about 300 are endemic ; Cape York Peninsula supports about 3000 species of native plants including at least 260 endemic species (Abrahams et al 1995;Neldner and Clarkson 1995); and the appreciably smaller (~30,000 km 2 ) plateau of western Arnhem Land includes at least 170 endemic plant species (Woinarski et al 2006a).…”
Section: Peter Jacklynmentioning
confidence: 99%
See 2 more Smart Citations